Model-Based Calibration of a Robotic C-Arm System Using X-Ray Imaging - Thürauf, Sabine; Hornung, Oliver; Körner, Mario; Vogt, Florian; Knoll, Alois; Ali Nasseri, M. (Journal of Medical Robotics Research, 2018)
In interventional radiology or surgery, C-arm systems are typical imaging modalities. Apart from 2D X-ray images, C-arm systems are able to perform 2D/3D overlays. For this application, a previously recorded 3D volume is projected on a 2D X-ray image for providing additional information to the clinician. The required accuracy for this application is 1.5mm. Such a spatial accuracy is only achievable with C-arms, if a calibration is performed. State-of-the-art approaches interpolate between values of lookup tables of a sampled Cartesian volume. However, due to the non-linear system behavior in Cartesian space, a trade-off between the calibration effort and the calibrated volume is necessary. This leads to the calibration of the most relevant subvolume and high calibration times. We discuss a new model-based calibration approach for C-arm systems which potentially leads to a smaller calibration effort and simultaneously to an increased calibrated volume. In this work, we demonstrate that it is possible to calibrate a robotic C-arm system using X-ray images and that a static model of the system is required to achieve the desired accuracy for 2D/3D overlays, if re-orientations of the system are performed.
Created from Fastlane, Scopus look-up
Keywords: C-arm system; Robot calibration; X-ray